Changes in Individual Weight Status Based on Body Mass Index and Waist Circumference in Hong Kong Chinese - Ho, Lai Ming (PLoS One, 2015)
BACKGROUND: Weight change predicted diseases and mortality. We investigate 3-year changes in individual body mass index (BMI) and waist circumference in Hong Kong Chinese adults. METHODS: In the Population Health Survey, 7084 adults in 2003 (baseline) were followed up in 2006. Longitudinal anthropometric data were available in 2941 (41.5%) for BMI and 2956 for waist circumference. Weight status and central obesity were based on objectively measured BMI and waist circumference using Asian standards. RESULTS: Mean BMI (SD) increased from 22.8 (3.62) to 23.1 (3.95) (p<0.001) with 1.3 percentage point increase in prevalence of overweight and obesity (from 44.3% to 45.6%). One in 5 (22.0%) normal or underweight baseline respondents became overweight or obese and a similar proportion (24.8%) of overweight and obese respondents became normal or underweight. Prevalence of central obesity increased from 28.3% to 32.4% (p<0.001) with a non-significantly greater increase in women (30.0% to 38.1%) than men (23.0% to 26.1%) (p=0.63). A higher proportion of centrally obese respondents returned to normal (29.4%) than normal respondents developing central obesity (17.4%). CONCLUSIONS: This is one of the few studies in Chinese, which found dynamic longitudinal changes (increase/stable/decrease) in individual weight status and waist circumference. Future studies with better follow-up and investigating the causes of such changes are warranted.